Availability based trust evaluation model for MANET - ZHAO Xi-bin1; YOU Zhi-yang1; ZHAO Zhi-feng3 (Tongxin xuebao)
ABTEM was presented, an availability based trust model, and many availability oriented security service can be obtained based on this model. The performance results show that malicious nodes can be successfully discovered in accordance with its malicious acts in the routing layer when apply ABTEM on the DSR protocol. Furthermore malicious nodes can be isolated to protect the network from the attack of them, and which will significantly increases system avail- ability.